Cybervictimization and emotional symptoms in adolescents: mediating role of psychological flexibility versus inflexibility - Molero Jurado, María del Mar; Martos Martínez, África; Pérez-Fuentes, María del Carmen; del Pino Salvador, Rosa María; Gázquez Linares, José Jesús (Frontiers in Psychology, 2025)
BackgroundCyberbullying significantly affects adolescents, increasing the risk of negative emotional symptoms. This study explores how psychological flexibility and inflexibility may mediate this relationship, focusing on adolescent mental health in the context of cyberbullying.MethodsA sample of 2,171 secondary school students, aged 11–18 years, was used to assess cyberbullying, emotional symptoms, and levels of psychological flexibility and inflexibility.ResultsCybervictimization showed a direct relationship with emotional symptoms and psychological inflexibility. Psychological flexibility was negatively associated with cybervictimization and positively associated with mental health, acting as a protective mediator against the association of cyberbullying.ConclusionPsychological flexibility emerges as a key factor in reducing the negative association of cybervictimization in adolescents. These findings highlight the importance of developing strategies to improve psychological flexibility in young people as a means to strengthen their resilience in the face of cyberbullying and its emotional consequences.